Effects of K(ATP) channel openers diazoxide and pinacidil in coronary-perfused atria and ventricles from failing and non-failing human hearts - Fedorov, Vadim V. (2011)
INTRODUCTION: This study compared the effects of ATP-regulated potassium channel (K(ATP)) openers, diazoxide and pinacidil, on diseased and normal human atria and ventricles. METHODS: We optically mapped the endocardium of coronary-perfused right (n=11) or left (n=2) posterior atrial-ventricular free wall preparations from human hearts with congestive heart failure (CHF, n=8) and non-failing human hearts without (NF, n=3) or with (INF, n=2) infarction. We also analyzed the mRNA expression of the K(ATP) targets K(ir)6.1, K(ir)6.2, SUR1, and SUR2 in the left atria and ventricles of NF (n=8) and CHF (n=4) hearts. RESULTS: In both CHF and INF hearts, diazoxide significantly decreased action potential durations (APDs) in atria (by −21±3% and −27±13%, p<0.01) and ventricles (by −28±7% and −28±4%, p<0.01). Diazoxide did not change APD (0±5%) in NF atria. Pinacidil significantly decreased APDs in both atria (−46 to - 80%, p<0.01) and ventricles (−65 to −93%, p<0.01) in all hearts studied. The effect of pinacidil on APD was significantly higher than that of diazoxide in both atria and ventricles of all groups (p<0.05). During pinacidil perfusion, burst pacing induced flutter/fibrillation in all atrial and ventricular preparations with dominant frequencies of 14.4±6.1 Hz and 17.5 ±5.1 Hz, respectively. Glibenclamide (10 μM) terminated these arrhythmias and restored APDs to control values. Relative mRNA expression levels of K(ATP) targets were correlated to functional observations. CONCLUSION: Remodeling in response to CHF and/or previous infarct potentiated diazoxide-induced APD shortening. The activation of atrial and ventricular K(ATP) channels enhances arrhythmogenicity, suggesting that such activation may contribute to reentrant arrhythmias in ischemic hearts.